KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH MENENGAH ATAS NEGERI 1 SUNGAI TEBELIAN PADA MATERI SPLDV - Pranando, R Andy; Hutagaol, Anita Sri Rejeki; Mizardi, Alvro (Kadikma, 2021)
This research is a qualitative descriptive study, with the aim of describing students' mathematical communication skills in solving problems using SPLDV material. The research subjects were students of SMA Negeri 1 Sungai Tebelian class X IPA I which consisted of 16 students. The number of subjects in this study consisted of three students who were categorized into three levels based on the division of students' communication skills. Based on the results of the study, it was concluded that the level of mathematical communication skills in solving math problems with SPLDV material was as follows: high-ability subjects achieved four indicators of mathematical communication, moderately capable subjects achieved three indicators of mathematical communication, low-ability subjects only achieved one indicator of mathematical communication. Of all students who were used as research subjects, more students belonged to the category of moderate ability as evidenced by the percentage of students who were moderately capable of 56%. Based on the results of these studies, improving mathematical communication skills is very important to achieve learning objectives.